IMPLEMENTASI KEBIJAKAN PENDIDIKAN AKHLAK DI MADRASAH ALIYAH NEGERI INSAN CENDEKIA KABUPATEN BANGKA - Doni; Hardian, Dafyar Eliadi; Darmojo, Hardjito S. (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
Ethical education plays a central role in shaping students' character, especially amidst the challenges of globalization and the rapid flow of digital information. This study aims to examine the implementation of moral education policies at the Insan Cendekia State Islamic Senior High School (MAN) in Central Bangka through George C. Edwards' public policy implementation theory, which highlights four key factors: communication, resources, implementer disposition, and organizational structure. The method used was a descriptive qualitative approach, and data collection techniques included interviews, observation, and documentation. The results indicate that the moral education policy has been implemented effectively through structured programs and adequate institutional support. Teachers, students, and the madrasah management demonstrate a positive commitment to implementing moral values. However, strengthening teacher competencies and collaboration with parents still needs to be improved to optimize and sustain competency outcomes. These findings indicate that MAN Insan Cendekia in Central Bangka has succeeded in building a strong foundation for moral education, which can serve as a model for other educational institutions. Keywords: Moral education, policy implementation, MAN Insan Cendekia.